2016
DOI: 10.1088/1748-9326/11/9/094010
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in vegetation greenness in China significantly altered annual evapotranspiration and water yield

Abstract: There has been growing evidence that vegetation greenness has been increasing in many parts of the northern middle and high latitudes including China during the last three to four decades. However, the effects of increasing vegetation greenness particularly afforestation on the hydrological cycle have been controversial. We used a process-based ecosystem model and a satellite-derived leaf area index (LAI) dataset to examine how the changes in vegetation greenness affected annual evapotranspiration (ET) and wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
91
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(105 citation statements)
references
References 85 publications
12
91
0
2
Order By: Relevance
“…At regional and continental scales, many studies based on satellite-derived data have established relationships between temporal and spatial changes in vegetation dynamics and climate change and variability [64][65][66][67][68]. For example, the mechanisms for the relationships of vegetation and climate warming in the Qinghai Tibet plateau have been extensively investigated.…”
Section: Effects Of Ai On the Increase In Vegetation Laimentioning
confidence: 99%
See 1 more Smart Citation
“…At regional and continental scales, many studies based on satellite-derived data have established relationships between temporal and spatial changes in vegetation dynamics and climate change and variability [64][65][66][67][68]. For example, the mechanisms for the relationships of vegetation and climate warming in the Qinghai Tibet plateau have been extensively investigated.…”
Section: Effects Of Ai On the Increase In Vegetation Laimentioning
confidence: 99%
“…Evidence exists that extreme climate events impact a broad range of ecosystems [75][76][77]. Moreover, according to IPCC climate models, it is likely that such extreme events will become more frequent and more intense in the future, although there is considerable uncertainty in climate model predictions [64]. The increase in temperatures on the Qinghai Tibet plateau has been much greater than other regions of the world in recent decades [78,79], and there may be a trend with more warming in the future, but uncertainty in precipitation [10,80].…”
Section: Potential Extreme Climate Effect On Laimentioning
confidence: 99%
“…Over the last three to four decades, using the satellite-observed leaf area index (LAI) or normalized difference vegetation index (NDVI), several researchers have found that the vegetation greenness has been increasing in most parts of the Northern Hemisphere, especially in China [1][2][3]. Increased vegetation greenness, resulting from watershed management projects such as afforestation, reforestation, and improved agricultural practices, can improve terrestrial ecosystem productivity [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Increased vegetation greenness, resulting from watershed management projects such as afforestation, reforestation, and improved agricultural practices, can improve terrestrial ecosystem productivity [4,5]. However, some studies have shown that vegetation greening can reduce watershed water yield (also referred to as streamflow or runoff); thus, it can reduce the water resources available for humans [1,6,7]. In fact, in arid and semi-arid areas, numerous studies have suggested that increased vegetation greenness can induce water demand conflicts, but few studies have investigated water yield responses on increased vegetation greenness in humid areas [4,8].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have investigated the relationships between land use patterns and basin hydrology and have found that the characteristics of basin hydrology vary among land use patterns due not only to the type of LULC (Wang et al, 2012;Jian et al, 2015;Duan et al, 2016) but also to the spatiotemporal heterogeneity of LULC (Chu et al, 2010;Liu et al, 2013). However, debate exists among ecohydrologists regarding the effects of past and ongoing land use changes because of the spatial and temporal complexity of hydrological processes (Lørup et al, 1998;López-Moreno et al, 2011;Alkama et al, 2013;Liu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%